Prostate cancer characteristics and outcome in renal transplant recipients: results from a contemporary single center study. Issue 8 (5th July 2016) - Pettenati, Caroline; Jannot, Anne‐Sophie; Hurel, Sophie; Verkarre, Virginie; Kreis, Henri; Housset, Martin; Legendre, Christophe; Méjean, Arnaud; Timsit, Marc‐Olivier
Abstract: Background: Prostate cancer (PCa) incidence is expected to increase in renal transplant recipients (RTR) with no clear nor contemporary data on management and oncological outcome. Methods: We conducted a retrospective single center study of RTR diagnosed with PCa after transplantation between 2000 and 2013. Demographics, PCa characteristics, and treatment were assessed. For each RTR in radical prostatectomy (RP) subset, we included 4 non‐organ transplant patients who underwent RP by the same surgeons, and compared pre‐operative and post‐operative oncological features, and biochemical recurrence (BCR) rate. Results: Twenty‐four RTR were included (PCa incidence 1.5%). Mean follow‐up was 47 months. PCa was mostly localized (n=21, 87.5%) with treatments including RP (n=16, 76.2%), brachytherapy (n=3, 14.3%), radiation therapy (n=1, 4.7%), and active surveillance (n=1, 4.7%). No graft loss due to PCa treatment was reported. Nineteen RTR with localized PCa (90.5%) were free from BCR. Considering RP subset, no difference in PCa characteristics at diagnosis and BCR rate was found between RTR (n=16) and control patients (n=64). Conclusions: Localized PCa following renal transplantation was not associated with adverse features as compared with non‐transplant patients. Standard treatments could be proposed to RTR with satisfying results both on oncological outcome and graft function.